Shaping the Character of Insan Kamil: Islamic Education Materials Through Character Education During the COVID-19 Pandemic - Masturin, M (Program Studi Pendidikan Agama Islam, 2022)
During the COVID-19 pandemic, teachers are experiencing difficulties in carrying out the learning process since they can only convey materials in the realm of cognition, causing the affective and psychomotor domains not to be achieved. In fact, the role of teachers in the learning process is needed to deliver the younger generation in shaping the nation's character. In the context of developing national character, the most important agenda concerns the collective reform of all components of the nation to make changes after undergoing each learning process. For this reason, this research focuses on Islamic education materials in shaping insan kamil through character education using effective and efficient learning during the COVID-19 pandemic. This learning was set with active learning to produce insan kamil who can answer the ummah's problems. The learning implementation began with planning, organizing, implementing, and evaluating. This study used a qualitative approach with a case study design, while the informants were determined by purposive sampling. The data collection techniques employed were in-depth interviews, participant observation, documentation, and focus group discussions. Checking the data validity was then carried out by extending the researcher's presence in the field, deepening observations, triangulation, peer discussion, checking members, transferability, dependence, and confirmability. This study’s results indicate that Islamic education can shape insan kamil through effective and efficient learning with active learning strategies, with blended learning during the COVID-19 pandemic.